Cell membrane-targeting NIR fluorescent probes with large Stokes shifts for ultralong-term transplanted neural stem cell tracking - Chen, Jing; Li, Dan; Li, Hongfu; Zhu, Kongkai; Shi, Leilei; Fu, Xuemei (Frontiers in Bioengineering and Biotechnology, 2023)
There is an emerging therapeutic strategy to transplant stem cells into diseased host tissue for various neurodegenerative diseases, owing to their self-renewal ability and pluripotency. However, the traceability of long-term transplanted cells limits the further understanding of the mechanism of the therapy. Herein, we designed and synthesized a quinoxalinone scaffold-based near-infrared (NIR) fluorescent probe named QSN, which exhibits ultra-strong photostability, large Stokes shift, and cell membrane-targeting capacity. It could be found that QSN-labeled human embryonic stem cells showed strong fluorescent emission and photostability both in vitro and in vivo. Additionally, QSN would not impair the pluripotency of embryonic stem cells, indicating that QSN did not perform cytotoxicity. Moreover, it is worth mentioning that QSN-labeled human neural stem cells held cellular retention for at least 6 weeks in the mouse brain striatum post transplantation. All these findings highlight the potential application of QSN for ultralong-term transplanted cell tracking.